Maqashid Al-Sharia Based Marketing Strategy of Imam As-Syatibi in Facing Business Competition: A Case Study of Arinna Hijab Ganding - Daroini, Sa'adatud; Hastriana, Anna Zakiyah (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This research analyzes the marketing strategy of Arinna Hijab Ganding based on Imam As-Syatibi's Maqashid Al-Sharia to increase competitiveness in a competitive market. Methodology: through a qualitative approach with a case study method, combining literature analysis of As-Syatibi's Maqashid Al-Sharia and observation of the marketing strategy implemented by Arinna Hijab Ganding involving 30 Arinna consumers with data collected through observation, interviews, and documentation. Result: The findings show how five important principles of Maqashid Al-Sharia (hifzh ad-din, hifzh an-nafs, hifzh an-nasl, hifzh al-mal) have been effectively integrated into the Company's marketing mix, resulting in differentiated value creation, strong customer trust, and sustainable business growth while maintaining sharia compliance. Findings: This study reveals that this strategy goes beyond profit maximization by incorporating ethical considerations such as fairness, transparency, and social responsibility. Novelty: This research highlights that this approach goes beyond profit maximization by incorporating ethical considerations such as fairness, transparency, and social responsibility, making it highly relevant for Islamic fashion businesses. Conclusions: By providing a practical model for operationalizing Islamic principles in marketing strategies, this research offers valuable insights for Shariah-compliant businesses seeking to balance commercial success with religious values in a competitive marketplace. Type of Paper: Research Article.